Peningkatan Hasil Belajar Matematika Menggunakan Model Pembelajaran Teams Game Tournament (TGT) di Kelas XI IPA 2 SMAN 10 Medan - Cindy Amelia Sitorus; Haryati Ahda Nasution; Nurdalilah Nurdalilah; Ummi Aulia; Dinda Qori Wahyuni (Departement of Mathematics Education, 2024)
In order to find out whether the Teams Game Tournament (TGT) style of learning may help students in class XI IPA 2 at SMA Negeri 10 Medan learn more about algebraic function derivatives in the 2023–2024 school year, this study was conducted. This study follows a two-cycle format typical of PTK, or Classroom Action Research. Twelve male and twenty female students from class XI IPA 2 at SMA Negeri 10 Medan made up the total of thirty-two participants in this research. The researchers in this study relied on observation and testing to compile their data. This study found that students in class XI IPA 2 at SMA Negeri 10 Medan learned more about the derivative of algebraic functions than in previous years. Both the percentage of teachers seeing student activities and the percentage of teachers observing teacher activities rose to 89.06% and 86.62%, respectively, in cycle II. Furthermore, student learning outcomes improved by 86.22 percent. Class XI IPA 2 students at SMA Negeri 10 Medan improved their performance in the 2023–2024 school year after using the Teams Game Tournament (TGT) style of instruction.